1980
DOI: 10.1029/gl007i011p00937
|View full text |Cite
|
Sign up to set email alerts
|

First measurements of total chlorine and bromine in the lower stratosphere

Abstract: A total halogen collection system employing ultra‐pure activated charcoal traps has been developed for use in the stratosphere aboard aircraft and balloon sampling platforms. Neutron activation techniques for low‐level chlorine, bromine, and iodine analysis within the activated charcoal sampling matrix were developed. Initial results from six aircraft flights and one balloon mission in the lower stratosphere are presented for latitudes ranging from 16°N to 67°N. Little variability was observed in twelve total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…The increase in the ratio also is not consistent with fly ash from the power plant located next to the proposed ILAW Disposal Site. Leaching of an 1l-cm-deep sample of fly ash yielded a C1/Br ratio of 41 (Table E.3, Appendix E), somewhat lower than the meteoric signature of 80 reported by Berg et al (1980). In contrast to the shallow fly ash sample, a deeper sample (61 cm) yielded a CM3r ratio of 382.…”
Section: B422mentioning
confidence: 62%
See 1 more Smart Citation
“…The increase in the ratio also is not consistent with fly ash from the power plant located next to the proposed ILAW Disposal Site. Leaching of an 1l-cm-deep sample of fly ash yielded a C1/Br ratio of 41 (Table E.3, Appendix E), somewhat lower than the meteoric signature of 80 reported by Berg et al (1980). In contrast to the shallow fly ash sample, a deeper sample (61 cm) yielded a CM3r ratio of 382.…”
Section: B422mentioning
confidence: 62%
“…They suggested that C1/Br ratios in precipitation vary geographically between 130 and 180 near the coast, to between 75 and 120 several tens to a few hundred kilometers inland, to as low as 50 several hundred kilometers inland. Berg et al (1980) measured a C1/Br ratio of 80 in the lower stratosphere at northern latitudes, which represents the total concentration of these anions in air. In the absence of specific measurements of meteoric C1/Br in the Pasco Basin, shallow porewater ratios should reflect the combined wetidry fallout ratio of meteoric CM%.…”
Section: B422mentioning
confidence: 99%
“…The increase in the ratio also is not consistent with fly ash from the power plant located next to the proposed ILAW Disposal Site. Leaching of an 11-cm-deep sample of fly ash yielded a Cl/Br ratio of 41 (Table E.3, Appendix E), somewhat lower than the meteoric signature of 80 reported by Berg et al (1980). In contrast to the shallow fly ash sample, a deeper sample (61 cm) yielded a Cl/Br ratio of 382.…”
Section: B423 Cl/br Ratiosmentioning
confidence: 58%
“…They suggested that Cl/Br ratios in precipitation vary geographically between 130 and 180 near the coast, to between 75 and 120 several tens to a few hundred kilometers inland, to as low as 50 several hundred kilometers inland. Berg et al (1980) measured a Cl/Br ratio of 80 in the lower stratosphere at northern latitudes, which represents the total concentration of these anions in air. In the absence of specific measurements of meteoric Cl/Br in the Pasco Basin, shallow porewater ratios should reflect the combined wet/dry fallout ratio of meteoric Cl/Br.…”
Section: B423 Cl/br Ratiosmentioning
confidence: 99%
“…Furthermore, the mixing ratios of all these gases were found to decrease with altitude, corroborating the hypothesis of photochemical decomposition in the stratosphere. Total chlorine measurements by a collection system were made by Berg et al (1980). These in situ measurements were later complemented by remotely sensed profiles.…”
Section: Corroboration and Falsification: Stratospheric Trace Gas Meamentioning
confidence: 99%